Analysis Of The Influence Of Liquidity On Profitability In Conventional Banks For The 2020-2022 Periode - SAMSINAR, Samsinar; Rizki Dwi Sulfani; Nurafni Oktaviyah (International Economic Conference of Business and Accounting, 2024)
This research aims to analyze the influence of liquidity on profitability in conventional banks listed on the Indonesia Stock Exchange for the 2020-2022 periode. The variables of this research are: (1) Profitability as the dependent variable (Y) which is measured by Return on Assets (2) Liquidity as the independent variable (X) which is measured by the Loan to Deposit Ratio (LDR). The population of this research is conventional banks listed on the Indonesia Stock Exchange, while the sample of this research is 30 companies taken using purposive sampling technique. Data collection was carried out using documentation techniques. Data analysis was carried out using the Simple Linear Regression Test, t Test, and Coefficient of Determination Test (r2). The results of this study show t count > t table or 15.434 > 1.658 and a significant value of 0.000 < 0.005. Based on the results of this analysis, it can be seen that liquidity (LDR) has a positive and significant influence on profitability. These results are in accordance with the proposed hypothesis, namely that liquidity (LDR) has a positive and significant influence on profitability. Keywords : Liquidity; Loan to Deposit Ratio; Profitability; Return on Assets.